2015
DOI: 10.1093/annonc/mdv369
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to circulating platinum is associated with late effects of treatment in testicular cancer survivors

Abstract: Cisplatin is an essential part of testicular cancer treatment. We investigated whether long-term exposure to circulating platinum (Pt) plays a role in the development of late effects in survivors. We assessed Pt decay in samples collected 1–13 years after chemotherapy. Renal function is a strong determinant of exposure to Pt. Higher exposure to Pt is associated with an increased prevalence of adverse effects hypogonadism and hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 22 publications
(28 reference statements)
1
59
1
Order By: Relevance
“…Previously published methods for quantifying low Pt concentrations in serum represented high-quality research assays but were difficult to implement for routine use in the clinical laboratory (4)(5)(6)14). Original methods were based on the measurement of Pt in plasma ultrafiltrates and used lengthy integration times to achieve the needed sensitivity (6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously published methods for quantifying low Pt concentrations in serum represented high-quality research assays but were difficult to implement for routine use in the clinical laboratory (4)(5)(6)14). Original methods were based on the measurement of Pt in plasma ultrafiltrates and used lengthy integration times to achieve the needed sensitivity (6).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well established that a cumulative dose of platinum administered intravenously is associated with a number of these adverse effects, it is also recognized that in European populations, platinum concentrations remain significantly increased in serum years after chemotherapy completion (2)(3)(4). Moreover, Brouwers et al (5) showed that these circulating platinating agents remain partly reactive.…”
Section: Impact Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypothesized ongoing damage of nerve fibers and/or blood vessels was supported by a comprehensive Dutch study on residual platinum, applied cumulative dose, and renal function combined with careful phenotyping of long-term outcomes like paresthesia, hypogonadism, high LDL cholesterol, and hypertension. 16 Hypertension was, among several other toxicities, significantly associated with higher exposure to residual platinum levels. We thereby assume the described association between hearing impairment and hypertension reflects two separate outcomes of the initial treatment, with hearing impairment being more stable after the initial damage caused by the peak cisplatin concentration, whereas hypertension probably was aggravated by ongoing endothelial damage by long-term circulating residual platinum.…”
mentioning
confidence: 99%